Evaluación del comportamiento del concreto elaborado con tereftalato de polietileno y polietileno de alta densidad en remplazo del agregado fino y valoración de propiedades mecánicas de los concretos elaborados con residuos termoplásticos (2020)
The objective of this work is to compile a state of art about the application of recycled thermoplastics to replace the raw materials used in the preparation of concrete and to evaluate the behavior of the concrete made whit two different types of recycled thermoplastic materials (High Density Polyethylene HDPE and polyethylene terephthalate PET), the concrete was made with a water / cement ratio of 0.50 and with a mix design made to resist a compressive strength of 21 MPa, a mix was made under normal standards, in order to use their results as a reference for the investigation and 3 mixtures where 25% of the volume of the fine aggregate was replaced with a similar volume: Mix 1 had 100% stone aggregates, Mix 2 had 75% stone aggregates and 25% PET waste, Mix 3 had 75% stone aggregates and 25% HDPE waste and Mix 4 had 75% stone aggregates and 12.5% PET waste and 12.5% HDPE waste. For each mixture, cylinders and beams were made to perform laboratory tests of: settlement, compressive strength at 7, 14 and 28 days, modulus of rupture at 28 days, indirect tensile strength at 28 days, chloride penetration at 28 days. The material used in this research was donated by thermoplastic waste collection and treatment industries, capable of shredding the material into particles with a maximum diameter of 1 cm. The elaborated mixtures presented good manageability in fresh state, with settlements between 7 and 10 cm, there was no segregation of the materials. For hardened concrete tests, similar results were presented in the compression and modulus of rupture tests, with respect to mix 1: mix 3 reached 75% of the expected strengths, while mix 2 only reached 35% and Mix 4 reached 55% of the expected strengths. When comparing the results of the indirect stress resistance test, with respect to the results obtained by mixture 1 (test mixture): mixture 3 reached 38% of the expected strengths, while mixture 2 and 4 only reached a 30% of the expected resistance. Finally, from the chloride ion penetration test, mixtures 1 and 2 obtained low permeabilities, mixture 2 presented a lower load transmission and therefore a lower permeability of the test, (71% with respect to mixture 1), while mixtures 3 and 4 presented moderate permeability, as the volume of HDPE increases in the percentage of replacement, an increase in the permeability of the test was presented (mixtures 3 and 4 presented an increase of 144% and 152%, respectively, at the lowest load with respect to mixture 1). It is therefore concluded that the use of crushed thermoplastics as a replacement for a percentage of fine aggregate for the preparation of concrete may have the potential to be used as a construction material for structural and non-structural elements.